Im-mediated Dante: Rachel Owen's Illustrations for the Commedia. (3rd April 2022) - Bowe, David
ABSTRACT: This article takes Owen's series of thirty-four completed illustrations for the Inferno and six illustrations from her unfinished Purgatorio series as a model of 'im-mediation'. In these images, the shift across media and time functions to collapse spectatorial distance between reader and text. Bowe reads this process as a paratextual one, making use of Genette's category for forms of extra-textual, mediating material, to engage with the dynamic relationship between these illustrations, Dante's Commedia, and the paratexts that it has accrued in the seven centuries since his death. The article argues that the unique first-person pilgrimage depicted in these illustrations allows for a new kind of profoundly affective, and shared, act of reading, while also demonstrating a critically-engaged interpretive drive grounded in the history of Dante illustration and commentary.